AL- ASYARIYAH (STUDI TENTANG PEMIKIRAN AL-BAQILLANI, AL-JUWAINI, AL-GHAZALI) - Hasyim, Muhammad Syarif (Hunafa: Jurnal Studia Islamika, 2005)
Theological thought of the Ashâarite founded by Abu Hasan al-Asyari develops through its theologians such as al-Baqillani, al-Juwaini, and al-Ghazali. Each of them has his own theological thought that differentiates him from other theologians. However, the three Ashâarite theologians remains to refer to the basic thought of the Ashaârite that make them different from Muâtazilite theologians, that is, they believe thatÂ  God has uncreated attributesÂ  negated by Muâtazilte.Â Kata Kunci: Pemikiran, Teologi, al-Asyâariyah